Pea and Chickpea Protein Concentrates: Quality Indicators - Valentina V. Kolpakova; Rusalia V. Ulanova; Denis S. Kulikov; Valentina A. Gulakova; Gennadiy V. Semenov; Ludmila V. Shevjakova (Техника и технология пищевых производств)
Protein deficiency in human and animal diet demands novel protein components, e.g., various leguminous concentrates. This article compares the quality indicators of food and feed protein concentrates obtained by biotechnological and biosynthetic methods from pea and chickpea flour. The research featured pea and chickpea protein concentrates; enzyme preparations Shearzym 500 L, Viscoferm L, Fungamyl 800 L, and Alcalase 2.4 L (Denmark); Saccharomyces and Geotrichum micromycetes yeasts. The protein concentrates were obtained from pea and chickpea flour using a new technology developed by the authors. The properties of the protein concentrates were studied by chemical, physicochemical, biochemical, and microbiological research methods. The research resulted in new protein concentrates for human diet and microbial-vegetable feed concentrates. The protein content was 83.22 ± 0.35% on dry basis in the chickpea protein concentrate and 71.78 ± 0.35% on dry basis in the pea concentrate. The indicator of biological value, adjusted for protein digestibility, was 96% for the pea protein concentrate and 76% for the chickpea protein concentrate. The resulting protein concentrates differed in the content of essential amino acids, copper, cobalt, manganese, and nickel, as well as in phenolic acids and their derivatives. The chickpea concentrate had a greater foaming capacity and lower foam stability, which correlated with a greater content of phenolic acids, their derivatives, parallel β-structures, and antiparallel protein 310-helices. Both the concentrates had the same results in assimilating whey carbohydrates by the consortium of Saccharomyces and G. micromycete. Both types of the dry feed biomass contained 61.68–64.10% protein on dry basis, while the biomasses with culture liquid contained 47.15–51.09% protein on dry basis. The biologically complete feed concentrates differed in the mass fraction of fat, soluble and insoluble fibers, minerals, and fatty acids. The amounts of phenolic acids and their derivatives (mg/g of protein) in the raw materials and the concentrates correlated with the optical density of their aqueous solutions at D590 nm and the color of the preparations (R = 0.895). The new pea and chickpea flour protein concentrates can be recommended as human food components, while the microbial-vegetable concentrates from pea and chickpea serum can improve the quality of raw materials of animal origin in animal feed.